Designing Urban Pervasive Systems. - Kostakos, Vassilis; O'Neill, Eamonn; Penn, Alan (Computer (00189162), 2006)
The article focuses on the pervasive systems in relation to the urban environment. It mentions the conceptual framework that they have used to the design of the pervasive systems related to the degrees of publicness including architectural spaces, interaction spaces and information sphere. The framework provides a simpler approach than more theoretical treatments of privacy wherein they consider the environment's constraints, features and opportunities. Moreover, it mentions the importance of the relationship between the people, barriers and space in determining the degree of publicness.